Distinct storage mechanisms of soil organic carbon in coniferous forest and evergreen broadleaf forest in tropical China. (1st October 2021) - Su, Fanglong; Xu, Shan; Sayer, Emma J.; Chen, Weibin; Du, Yue; Lu, Xiankai
Abstract: The impact of human activities on soil carbon (C) storage in tropical forests has aroused wide concern during the past decades, because these ecosystems play a key role in ameliorating global climate change. However, there remain uncertainties about how land-use history alters soil organic carbon (SOC) stability and storage in different forests. In this study, we measured the C content and mass distributions of soil aggregates, density fractions, mineral-bound C and microbial biomass C in the organic horizon, 0-10 cm and 10-20 cm soil layers in coniferous forest and evergreen broadleaf forest at Dinghushan Biosphere Reserve in tropical China. The broadleaf forest had larger SOC stocks than the coniferous forest, but the proportion of SOC stored in different density fractions at 0-10 cm soils was similar between forest types, while a greater proportion of SOC was stored in microaggregates in the coniferous forest. Most of the SOC was held as light fraction C in the organic horizon in the coniferous forest, whereas the concentrations of mineral-bound C were higher in the broadleaf forest. These findings indicate clear differences in the protection of SOC between broadleaf and coniferous forests growing on the same soil type. We propose that historic conversion of broadleaf forest to coniferous forest has reduced soil C sequestration capacity by altering the diversity and quality of plant inputs to the soil, which in turn affected macroaggregate formation, soil chemical properties and microbial biomass. Our results thus demonstrate that changes in forest tree species composition could have long-lasting effects on soil structure and carbon storage, providing crucial evidence for policy decisions on forest carbon sink management. Highlights: Historic conversion of broadleaf forest to coniferous forest altered distribution of soil aggregates and density fractions. Broadleaf forest had a greater proportion of mineral-bound C and macroaggregate-C than that in coniferous forest. Translating tropical broadleaf forest to coniferous forest reduced SOC stocks and C sequestration capacity.